The role of orexins/hypocretins in alcohol use and abuse: an appetitive-reward relationship - Kim, Andrezza K.; Brown, Robyn M.; Lawrence, Andrew J. (Frontiers in Behavioral Neuroscience, 2012)
Orexins (hypocretins) are neuropeptides synthesized in neurons located in the lateral, perifornical and dorsomedial hypothalamus. These neurons innervate many regions in the brain and modulate multiple other neurotransmitter systems. As a result of these extensive projections and interactions orexins are involved in numerous functions, such as feeding behavior, neuroendocrine regulation, the sleep-wake cycle and reward-seeking. This review will summarise the literature to date which has evaluated a role of orexins in the behavioral effects of alcohol, with a focus on understanding the importance of this peptide and its potential as a potential therapeutic target for alcohol use disorders.